LKB1 and AMPKα1 are required in pancreatic alpha cells for the normal regulation of glucagon secretion and responses to hypoglycemia - Gao Sun; Gabriela da Silva Xavier; Tracy Gorman; Claire Priest; Antonia Solomou; David J. Hodson; Marc Foretz; Benoit Viollet; Pedro-Luis Herrera; Helen Parker; Frank Reimann; Fiona M. Gribble; et al. (Elsevier, 2015)
Aims/Hypothesis: Glucagon release from pancreatic alpha cells is required for normal glucose homoeostasis and is dysregulated in both Type 1 and Type 2 diabetes. The tumour suppressor LKB1 (STK11) and the downstream kinase AMP-activated protein kinase (AMPK), modulate cellular metabolism and growth, and AMPK is an important target of the anti-hyperglycaemic agent metformin. While LKB1 and AMPK have emerged recently as regulators of beta cell mass and insulin secretion, the role of these enzymes in the control of glucagon production in vivo is unclear. Methods: Here, we ablated LKB1 (αLKB1KO), or the catalytic alpha subunits of AMPK (αAMPKdKO, -α1KO, -α2KO), selectively in ∼45% of alpha cells in mice by deleting the corresponding flox'd alleles with a preproglucagon promoter (PPG) Cre. Results: Blood glucose levels in male αLKB1KO mice were lower during intraperitoneal glucose, aminoimidazole carboxamide ribonucleotide (AICAR) or arginine tolerance tests, and glucose infusion rates were increased in hypoglycemic clamps (p < 0.01). αLKB1KO mice also displayed impaired hypoglycemia-induced glucagon release. Glucose infusion rates were also elevated (p < 0.001) in αAMPKα1 null mice, and hypoglycemia-induced plasma glucagon increases tended to be lower (p = 0.06). Glucagon secretion from isolated islets was sensitized to the inhibitory action of glucose in αLKB1KO, αAMPKdKO, and -α1KO, but not -α2KO islets. Conclusions/Interpretation: An LKB1-dependent signalling cassette, involving but not restricted to AMPKα1, is required in pancreatic alpha cells for the control of glucagon release by glucose.